12-MONTH PREVALENCE AND TREATMENT OF MENTAL DISORDERS IN LEBANON: A National Epidemiologic Survey - Karam, Elie G. (2006)
BACKGROUND: Mental disorders are thought to account for a significant portion of disease burden throughout the world. However, no national studies have been conducted to assess this assumption in the Arab world. METHODS: As part of the World Health Organization (WHO) World Mental Health (WMH) Survey Initiative, a nationally representative psychiatric epidemiological survey of n = 2857 adults (ages 18+) was carried out in Lebanon (the Lebanese Evaluation of the Burden of Ailments and Needs Of the Nation: LEBANON). Twelve-month prevalence and severity of DSM-IV disorders and treatment were assessed with the WHO Composite International Diagnostic Interview (CIDI, Version 3.0). Information was also obtained about socio-demographics and exposure to traumatic events in the Lebanon wars. FINDINGS: One-sixth (17.0%) of respondents met criteria for at least one 12-month DSM-IV/CIDI disorder, 27.0% of whom were classified serious and an additional 36.0% moderate. Nearly half of respondents had a history of exposure to war-related traumatic events. Significantly elevated odd-ratios (OR) of mood, anxiety and impulse-control disorders were associated with two (OR = 2.0-3.6) or more (OR = 2.2-9.1) war-related traumatic events, resulting in substantially higher proportions of moderate or severe 12-month mental disorders among respondents exposed to multiple war-related traumata (16.8-20.4%) than other respondents (3.3-3.5%). Only 10.9% of respondents with 12-month disorders obtained treatment. Two-thirds of treatment was provided in the general medical sector. INTERPRETATION: Mental disorders are common in Lebanon. Prevalence is similar to WMH surveys in Western Europe. Unmet need for treatment is considerably higher in Lebanon than in Western countries.